2012
DOI: 10.1186/ar3812
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of endothelial cell activity by inhibition of tumor necrosis factor-alpha

Abstract: IntroductionTNFα is a proinflammatory cytokine that plays a central role in the pathogenesis of rheumatoid arthritis (RA). We investigated the effects of certolizumab pegol, a TNFα blocker, on endothelial cell function and angiogenesis.MethodsHuman dermal microvascular endothelial cells (HMVECs) were stimulated with TNFα with or without certolizumab pegol. TNFα-induced adhesion molecule expression and angiogenic chemokine secretion were measured by cell surface ELISA and angiogenic chemokine ELISA, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
18
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 52 publications
(75 reference statements)
4
18
0
2
Order By: Relevance
“…In contrast, TNF non-responders had a markedly elevated number of circulating TH-17 cells and serum IL-17 levels suggesting that TNF is important for TH-17 cells differentiation in RA [64]. Others have shown that TNF can impact RA angiogenesis by modulating endothelial cell secretion of pro-angiogenic adhesion molecules (E-selectin, ICAM1 and VCAM1) and chemokines (CXCL1, CXCL5, CXCL8, CCL2 and CCL5) [65,63]. …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, TNF non-responders had a markedly elevated number of circulating TH-17 cells and serum IL-17 levels suggesting that TNF is important for TH-17 cells differentiation in RA [64]. Others have shown that TNF can impact RA angiogenesis by modulating endothelial cell secretion of pro-angiogenic adhesion molecules (E-selectin, ICAM1 and VCAM1) and chemokines (CXCL1, CXCL5, CXCL8, CCL2 and CCL5) [65,63]. …”
Section: Introductionmentioning
confidence: 99%
“…In RA hyperexpression of ICAM-1 and VCAM-1 on endotheliocytes, macrophages and fibroblasts, provided by the stimulation of pro-inflammatory cytokines, favors chronisation of inflammatory reaction in joint tissues [8,20].…”
Section: Abstract: Rheumatoid Arthritis Immunoglobulins Superfamily mentioning
confidence: 99%
“…1 представлены основные эффекты цитокинов, участвующих в развитии РА. Провоспалительные цитоки-ны, секретируемые макрофагами (ФНОα, ИЛ1, ИЛ6, ИЛ8, ИЛ18 и фактор, ингибирующий миграцию макрофа-гов), играют центральную роль в ангиогенезе при РА как за счет прямого влияния на эндотелиальные клетки, так и опосредованно, стимулируя выработку проангиогенных факторов различными типами клеток синовиальной обо-лочки [7,[10][11][12][13].…”
unclassified
“…Процессы неоангиогенеза неразрывно связаны с вос-палением при РА, и наличие этой связи доказано во мно-гих исследованиях [8][9][10][11][12]. Учитывая ведущую роль этих патогенетических механизмов, проводились работы, по-священные изучению связи провоспалительных цитоки-нов и маркеров ангиогенеза [16], с УЗ-признаками, харак-теризующими состояние синовиальной оболочки при РА (табл.…”
unclassified